Some remarkably common, but undescribed, Megaselia Rondani (Diptera: Phoridae) from northwestern Costa Rica - Brown, Brian V. (Zootaxa, 2022)
A collection of 16,521 barcoded phorid flies from Área de Conservación Guanacaste (ACG) in northwestern Costa Rica contains 1,498 recognized BINs (Barcode Index Numbers) in the BOLD database. These BINs were identified to genus, based on photographs, and the collection was found to be composed largely (893/1,498=60%) of specimens of the enormous genus Megaselia Rondani. The nine most common ACG Megaselia, represented by 100 or more specimens each, are briefly described, and diagnosed largely based on DNA barcodes. This study is a prelude and pilot to naming the many less-common species in a similar format.